Citizenship Ceremonies as an Opportunity for Behaviour Change: A Quasi-experiment with London Councils. Issue 2 (2nd April 2020) - John, Peter; Blume, Toby; Saggar, Kieran
ABSTRACT: Research on pro-social behaviours has mainly concentrated on individually-tailored interventions, such as Get Out the Vote (GOTV) campaigns, rather than collective arenas where information and messages are experienced jointly. Citizenship ceremonies, in which new UK citizens are required to participate, provide a timely and unique opportunity to promote civil behaviours in a group context. The research for this paper, based on a quasi-experiment comparing ceremonies within London local authorities, tests whether providing volunteering opportunities and incorporating behavioural science interventions into the design of the ceremonies increase voter registration, volunteering, and blood donation intentions. Survey results show that providing volunteering opportunities generates an interest in registering to volunteer and donating blood, while the addition of behavioural interventions boosts intention to volunteer and registering to vote, with statistically significant effects of the behavioural interventions on the summed outcome measure. The research findings are a promising foundation for further tests using randomised controlled trials.